Identification of critical factors for effective Strategic Investment Decisions. (21st January 2009) - Chen, Jau-Rong; Wang, Jung-Te; Chou, Tzu-Chuan
The main objective of this study was to explore the factors which may impact on the effectiveness of Strategic Investment Decisions. The empirical testing was based on the sample from Taiwanese enterprises. Seven critical factors were identified including the scope of involvement in the project formulation process, the competitive position of the company, the growth rate of the market related to the project, the perceived accuracy of the productivity index, the perceived accuracy of profit, the radicalism of the consequences and the financial state of the company. The findings of this study and future research directions were also discussed.